Data management of protein interaction networks - Cannataro, Mario, 1964-; Guzzi, Pietro Hiram, 1980- (Hoboken, New Jersey : John Wiley & Sons, 2011)
'Current PPI databases do not offer sophisticated querying interfaces and especially do not integrate existing information about proteins. Current algorithms for PIN analysis use only topological information, while emerging approaches attempt to exploit the biological knowledge related to proteins and kinds of interaction, e.g. protein function, localization, structure, described in Gene Ontology or PDB. The book discusses technologies, standards and databases for, respectively, generating, representing and storing PPI data. It also describes main algorithms and tools for the analysis, comparison and knowledge extraction from PINs. Moreover, some case studies and applications of PINs are also discussed'--
Keywords: Protein-protein interaction -- Information resources; Information resources management